2 - L’impact de la Culture sur les Dynamiques Entrepreneuriales : Application au Cas d’une Banque Tunisienne - Fakhri Issaoui, (African Sociological Review, 2020)
The main objective of this work is to examine the effects of culture on the performance of banks using the UIB as a case study. Our choice of problematic is motivated by two essential reasons. First, the ascending importance of the notion of Corporate Culture (or corporate culture) as a new determinant of banking performance (which is added to traditional determinants like capital, work, information, technical progress, etc.). Second, the relative scarcity of similar studies in the Tunisian context and which this work aims to address at least partially. As a result of our theoretical and empirical work, we have shown that as much as financial institutions strengthen culturality within their organizations, as much they become more efficient. Empirical work based on questionnaire for UIB staff has shown that this bank has invested in building a typical culture capable of uniting employees around an increasingly large community.